An Ego Depletion Perspective Linking Political Behavior to Interpersonal Deviance - Xiu, Jing; Zheng, Junwei; Li, Zhigang; Zhang, Zhenduo (Frontiers in Psychology, 2022)
A political act is a typical self-serving behavior that works to promote or protect self-interest. However, limited research explores its relationship with daily downstream behavior. Based on the ego depletion theory, the present study attempts to clarify when and how daily political acts will be transformed into interpersonal deviance. We collected 760 cases nested in 152 full time workers in mainland China through the experience sampling method. Via a multilevel structural equation model and hierarchical linear model, we tested the mediated moderation model. The results showed that political acts correlated with interpersonal deviance on a daily basis. Moral self-efficacy buffers the relationship between political acts and interpersonal deviance, whereas chronic job strain amplifies the relationship. Furthermore, moral self-efficacy can mediate the moderating role of chronic job strain.